Skin and vitamin D: New aspects for dermatology - Zahoor, Mahwish; Shaukat, Shehla; Afzal, Amina; Hussain, Ijaz (Journal of Pakistan Association of Dermatologists, 2020)
Vitamin D is a fat-soluble steroid hormone, traditionally known as the â€œsunshineâ€ vitamin. It is obtained by photo exposure, diet or supplements and is crucial for human health. It is globally known for its importance in calcium homeostasis, bone health and antirachitic activity. In recent years, it has been known that synthesis, activity and metabolism of vitamin D is greatly linked to skin. Vitamin D has been recently implicated in a plethora of medical illnesses.